(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
To inculcate good values and traditions in the life of society, in particular, the culture of reading, which is of incomparable importance in increasing the spiritual and intellectual potential of our people, especially the younger generation, their thinking and worldview, in teaching. special attention is paid to improving the development of a well-rounded personality.